2023
DOI: 10.1021/acsnano.3c00227
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Neutrophil Extinguisher Targets Cascade Immune Pathways of Macrophages for Alleviating Cytokine Storm in Pneumonia

Anwei Zhou,
Kerong Chen,
Ya Gao
et al.

Abstract: Cytokine storm is a common complication of COVID-19 pneumonia and has been proven to contribute to high mortality rates. However, current treatment approaches exhibit limited potential to balance immune response and overproduction of inflammatory cytokines, leading to poor therapeutic outcomes. Herein, a smart bioengineered neutrophil, Extinguisher, composed of live neutrophils encapsulating the liposome formulation of NF-κB suppressor MLN4924 and STING inhibitor H-151 (Lip@MH), is developed for alleviating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…82 – 84 Also, some studies have found that liposomes can neutralize inflammation or regulate and mitigate the cytokine storm against infections and their resulting inflammatory responses. 85 With the action of liposomes, anti-inflammatory drugs were transported to macrophages, inhibiting signaling pathways involved in inflammation and thereby calming the cytokine storm. 86 However, some studies have reported that drug-loaded liposomes can induce inflammatory responses during infection.…”
Section: Advanced Nanotechnologiesmentioning
confidence: 99%
“…82 – 84 Also, some studies have found that liposomes can neutralize inflammation or regulate and mitigate the cytokine storm against infections and their resulting inflammatory responses. 85 With the action of liposomes, anti-inflammatory drugs were transported to macrophages, inhibiting signaling pathways involved in inflammation and thereby calming the cytokine storm. 86 However, some studies have reported that drug-loaded liposomes can induce inflammatory responses during infection.…”
Section: Advanced Nanotechnologiesmentioning
confidence: 99%
“…Once at the target site, it releases Lip@MH, facilitating the transport of anti-inflammatory agents into macrophages. The dual action effectively inhibits NF-κB and STING-mediated inflammatory pathways, leading to a notable reduction in cytokine production [ 163 ]. Remarkably, in animal studies, extinguishers demonstrated selective accumulation at the pneumonia site and tangible mitigation of the cytokine storm through regulating NF-κB/STING signaling pathways, ultimately resulting in improved therapeutic outcomes [ 163 ].…”
Section: Nf-κb Pathway: a Pharmacological Target In Covid-19mentioning
confidence: 99%